What Determines Women's Labor Supply? The Role of Home Productivity and Social Norms - Farzana Afridi; Monisankar Bishnu; Kanika Mahajan (Institute of Labor Economics (IZA), 2019)
We highlight the role of home productivity in explaining the gender gap in labor force participation (LFP), and the non-monotonic relationship of women's LFP with their education in developing countries (India) in contrast to the developed economies (United Kingdom, U.K.). We construct a model of couples' time allocation decisions allowing for both market and home productivity to improve with own education. Our theoretical predictions match the data for India at low levels of women's education but over-predict labor supply at higher levels, unlike the U.K.. Incorporating constraints imposed by social norms regarding the gendered division of labor shows that norms can act as a binding constraint, producing much smaller increases in women's labor supply to market work at higher education levels in transition economies. Our analysis suggests that home productivity, along with social norms regarding couples' time allocation, can be critical determinants of women's labor supply in developing countries.
Keywords: E24; J22; J16; 330; women's labor supply; social norms; home production; education; India; U.K.